Supramolecular electrocatalysis of a highly efficient oxygen evolution reaction with cucurbit[6]uril. (11th November 2021) - Dai, Xin; Jin, Xian-Yi; Ge, Qingmei; Zhao, Jie; Liu, Mao; Cong, Hang; Tao, Zhu; Jiang, Nan
Abstract : A supramolecular ternary electrocatalyst, fabricated via the stepwise-coating of polypyrrole, rGO and cucurbit[6]uril, was developed for highly efficient oxygen evolution reaction with full electrochemical performance. Abstract : A supramolecular strategy was developed for electrocatalytic water splitting in the presence of a macrocyclic compound. The improvement in the oxygen evolution reaction (OER) was observed on the surface of an electrode modified via the facile layer-by-layer assembly of polypyrrole (PPy), reduced graphene oxide (rGO) and cucurbit[6]uril (Q[6]) in sequence. The electrochemical performance was evaluated, and the results indicate the remarkable activity of the proposed supramolecular electrocatalyst toward the OER in alkaline media. The morphology and chemical structure of the electrocatalyst were estimated before and after the OER process. Linear sweep voltammetry measurements suggested that a current density of 10 mA cm −2 at an overpotential of 377 mV was achieved, which is very close to the value of IrO2 under the same conditions, and the calculated Tafel slope of 167 mV dec −1 and electrochemical impedance spectroscopy results imply that a fast charge transfer occurs on the electrode with the functionalization of Q[6]. The developed catalyst could be considered as a potential alternative material for high-efficiency electrocatalytic OER.